Identification of Active Surface Species in Molten Carbonates Using in situ Raman Spectroscopy - Zhang, Peng; Wu, Tao; Huang, Kevin (Frontiers in Energy Research, 2021)
Here we report the results of a study on active surface species of a pristine and modified (Li-Na)2CO3 eutectic using in situ Raman spectroscopy technique. The effects of gas compositions, temperature, time, and alkaline earth have been systematically studied. The species of CO42–, HCO4–, and C2O52– are identified as the three major active species on the surface of (Li-Na)2CO3 eutectic by a combined Raman spectroscopy and theoretical density functional theory calculations. The results further reveal that CO42–, HCO4–, and C2O52– are preferably formed in the presence of O2, H2O, and high CO2 concentration. With the addition of Ba to the pristine (Li-Na)2CO3 eutectic, the Raman CO42–/HCO4– shifts become more pronounced.